2012
DOI: 10.1001/archinternmed.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk for Angioedema Associated With the Use of Drugs That Target the Renin-Angiotensin-Aldosterone System

Abstract: Background: Although certain drugs that target the renin-angiotensin-aldosterone system are linked to an increased risk for angioedema, data on their absolute and comparative risks are limited. We assessed the risk for angioedema associated with the use of angiotensinconverting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and the direct renin inhibitor aliskiren.Methods: We conducted a retrospective, observational, inception cohort study of patients 18 years or older from 17 health plans pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 21 publications
13
101
3
3
Order By: Relevance
“…While angioedema is described during the first week of exposure in over half of cases, it can occur any time during the course of therapy. [11][12][13] A large retrospective study found that two-thirds of ACEI associated angioedema episodes occur within the first three months of therapy 11 while case reports have documented angioedema episodes that began after years of stable therapy. 14,15 A better understanding of when angioedema can occur from ACEI is needed to guide patient care.…”
Section: Introductionmentioning
confidence: 99%
“…While angioedema is described during the first week of exposure in over half of cases, it can occur any time during the course of therapy. [11][12][13] A large retrospective study found that two-thirds of ACEI associated angioedema episodes occur within the first three months of therapy 11 while case reports have documented angioedema episodes that began after years of stable therapy. 14,15 A better understanding of when angioedema can occur from ACEI is needed to guide patient care.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, the RAAS modulator is known to produce potential side effects, such as angioedema, hypotension and acute pancreatitis by angiotensin receptor blocker, renin inhibitor and ACE inhibitors. [30][31][32] ACE inhibitors and angiotensin receptor blockers both cause cough and angioedema which produces cardiovascular risk in human. 33,34 Angiotensin II is more prone to causing vasoconstriction along with ischemic neuropathy by activation of the angiotensin receptor in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Although ARBs may be considered as alternative therapy for patients who have developed angioedema while taking an ACE inhibitor, there are some patients who have also developed angioedema with ARBs, and caution is advised when substituting an ARB in a patient who has had angioedema associated with use of an ACE inhibitor. [67][68][69][70] Clinical Recommendation(s) 2013 ACCF/AHA Guideline for Management of Heart Failure 24 1. ACE inhibitors are recommended in patients with HFrEF and current or prior symptoms, unless contraindicated, to reduce morbidity and mortality.…”
Section: The Measures and Specifications Are Provided "As Is" Withoutmentioning
confidence: 99%